Institutional economics approach in tourism: A review of economic philosophy - Karim, Syahrul; Kusuma, Bambang Jati; Farida, Farida (Journal of Rural Tourism, 2024)
Purpose - This article reviews the application of Institutional Economics in the tourism sector, evaluating its ability to address the limitations of conventional economic theories and enhance understanding of tourism’s social and economic impacts.Methodology/Design/Approach - Using a theoretical approach, the article explores how Institutional Economics can overcome traditional economic theories' limitations and contribute to more inclusive and sustainable tourism policies.Finding - Institutional Economics offers valuable insights into tourism, addressing gaps in conventional models. It promotes a more comprehensive understanding of tourism’s impacts, particularly in sustainability and inclusivity, aiding the development of policies that prioritize long-term societal welfare and economic growth.Originality/Value - This article introduces a novel perspective by applying Institutional Economics to tourism, emphasizing the need for sustainable and inclusive tourism policies that focus on societal and economic well-being.